Table of Content - - (Journal of engineering sciences and information technology, 2025)
Table of Content: 1. The Role of the ChatGPT AI Application in Enhancing the Performance of Computer Trainers at the Technical College in Mecca Eng. Sami Munahi Al-Meqati 2. The Effect of Iron Slag Powder Addition on the Performance of Self-Compacting Concrete lecturer Haifa Ali Abu Haliga, Abdul Hadi Mohamed Alebrahim, Hamed Munir Al-Mobaid 3. Large Language Models in Intellectual Discourse: An Empirical Evaluation of Performance Dev Abdennacer Elbasri